Extracorporeal photopheresis combined with pentostatin in the conditioning regimen for canine hematopoietic cell transplantation does not prevent GVHD - Bethge, Wolfgang (2014)
Extracorporeal photopheresis (ECP) and the purine analog pentostatin exert potent immunomodulatory effects. We evaluated the use of these treatment modalities to prevent GVHD in a canine model of unrelated dog leukocyte antigen mismatched hematopoietic cell transplantation (HCT), after conditioning with 920 cGy total body irradiation (TBI). We have shown previously in this model that 36/40 dogs given methotrexate (MTX) alone as postgrafting immunosuppression engrafted and that 25 of 40 dogs had severe GVHD and median survival of 21 days. In the current study, 9 dogs received conditioning with 920 cGy TBI and postgrafting MTX either with ECP on days −2 to −1 alone (n=5) or ECP on days −6 and −5 combined with 2 doses of pentostatin (days −4 to −3) (n=4). Seven of 9 dogs achieved engraftment. Six dogs developed severe acute GVHD (4 in the group with ECP alone and 2 with Pentostatin and ECP). We failed to demonstrate a positive impact of ECP and pentostatin for the prevention of GVHD compared to historical control dogs.